Aspects of Environmental Health in the Control of Emergency Response to Coronavirus Disease (COVID-19) in Hospital Emergency COVID-19 the Province of DKI Jakarta - Lailia Ayu Rachmawati (Media Gizi Kesmas, 2021)
ABSTRACTBackground: Coronavirus Disease Of 2019 (COVID-19) has been declared by the WHO as a pandemic and Indonesia have expressed COVID-19 as a disaster non-natural form of the outbreak of the disease. The increasing cases COVID-19 in Indonesia, The Provincial government of DKI Jakarta building of Emergency Hospital COVID-19. The emergency hospital to consider the health aspects of the environment to minimize the risk of disease transmission. The purpose of this study is to determine the aspects of environment health in Emergency Hospital COVID-19 of Provinsi DKI Jakarta.Objectives: Analyzing the environmental health aspects of the COVID-19 emergency hospital in DKI Jakarta ProvinceMethods: We used descriptive research with secondary data from online seminar by web, guidebook dan regulation about of Environmental Health of Emergency Hospitals COVID-19, issued by the Ministry of Health of the Republic of Indonesia.Results: Aspects of environmental health at the Emergency Hospital COVID-19 of Province DKI Jakarta such as : Availability of clean water and drinking water at the hospital with assuming a capacity of 3000 patients, the hospital requires 1,500 m3 of water/ day and 15 m3 of drinking water/ day. Available means the toilet and the sink in accordance with the number of units. Domestic solid waste management with temporary storage of Kemayoran with capacity of 280 m3 and the processing of organic waste and inorganic. Medical solid waste management in collaboration with third parties to be destroyed by incinerators. Liquid waste management with wastewater treatment plant (WWTP). Vector control and Rodent at the emergency hospital is done make of insect killer, trapping, spraying, and fogging. The provision of a kitchen emergency response chaired by nutritionist and food ingredients always be checked before it is processed.Conclusions: All aspects of environmental health at Emergency Hospital COVID-19 of Province DKI Jakarta have met the requirements according to the Regulation of Ministry of Health of The Republic Indonesia  Number 7 at 2019 about Environmental Health in Hospital.Keyword: environmental health, hospital, COVID-19